Ocular manifestations of dermal paraneoplastic syndromes - Zdebik, Alexander; Lantzsch, Hanka; Buhles, Norbert; Zdebik, Natalia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Dermal paraneoplastic syndromes are non-malignant disorders, caused indirectly by the increase in growth factors or as immunological reactions, which lead to a variety of inflammatory, hyperkeratotic or proliferative skin reactions. They can occur as facultative or obligate paraneoplastic dermatoses, which are associated with oncological processes (solid tumours or hematologic diseases). The recognition of paraneoplastic skin disorders can accelerate proper diagnosis and determine better prognosis for the patient and is also important to clinicians because it is often the first symptom of life-threatening malignancies. Many of them may also cause ocular changes that can lead to serious complications including perforation of the eye bulb, vascular changes in the retina resulting in vision loss and demand multidisciplinary co-operation with an ophthalmologist. This manuscript is a review of the literature about eye disorders in association with dermal paraneoplastic syndromes.